Population-based Research in AYUSH: Lessons from Study among Particularly Vulnerable Tribal Groups to Determine Burden of Sickle Cell Disorders - Nisanth K. M. Nambison; Abhishek Dhar Dwivedi; Sanjeev Kumar; Garima Goel; Pankaj Prasad; Gyanendra Singh; S. Rajasubramaniam; Ravindra Kumar (Journal of Applied Sciences and Clinical Practice)
Background: Population-based research (PBR) plays a critical role in generating externally valid evidence and engaging local communities in health interventions. However, there is a lack of examples in the field of homeopathy. This study describes the transformation of a Homoeopathy Medical College and Hospital to initiate and sustain PBR. The focus was on Particularly Vulnerable Tribal Groups (PVTGs) of India, with a specific emphasis on sickle cell disorders (SCD), a significant health concern among tribal populations in Madhya Pradesh (MP). Aims and Objectives: The study aimed to estimate the burden of SCD among PVTGs in MP and evaluate the effectiveness of homeopathy as an adjuvant therapy. Materials and Methods: A sequential explanatory mixed methods design was used, incorporating document analysis, a structured literature review on PubMed, and a search of homeopathy journals and conference abstracts. A community-based cross-sectional survey was conducted using probability proportional to size (PPS) sampling in four districts of MP. Blood samples were collected for SCD diagnosis, and ethical clearance was obtained from the Government Homoeopathic Medical College and Hospital, Bhopal. Results: The study surveyed 27,892 individuals (mean age 27.71 ± 18.11 years) from the Baiga and Bhariya PVTGs across 346 villages. Out of these, 23,320 participants were deemed eligible for screening. Sickle cell solubility tests revealed that 9.4% (n = 2195) of participants were suspected to have SCD. A comprehensive module and Standard Operating Procedure (SOP) on PBR in homeopathy was developed for future researchers. Conclusion: This study provides a blueprint for implementing PBR in homeopathy, particularly with vulnerable populations. The use of mixed methods research in PBR, especially for assessing homeopathy’s role in managing SCD, is valuable for extending research in underrepresented populations.